Difference of Bacterial Community Structure in the Meadow, Maize, and Continuous Cropped Alfalfa in Northeast China - Yang, Zhao; Xu, Yanxia; Li, Hong; Li, Shasha; Wang, Xiaolong; Chai, Hua (Frontiers in Microbiology, 2022)
Maize and alfalfa (Medicago sativa L.) have been used extensively in the animal husbandry to compensate for the lack of livestock and fodder yields in the chilly northeast of China. Little is known, however, about the impact on soil characteristics of consecutive plantings in the various crops and of alfalfa. In this research, the soil characteristics, community diversity and structure of the bacterial community of the meadow, maize, and alfalfa continues cropping fields (i.e., 6, 10, 14, 20, and 30 years) were measured. The results showed that maize cropping and continuous cropping of alfalfa increased the soil bacterial alpha diversity compared with meadow cropping, and alpha diversity also increased in the long-term continuous planting system. Soil pH, total P, available P, total K, and NO3- content were significant soil variables impacting the structure of soil bacterial communities in different plant types and different alfalfa continuous cropping system. In addition, the relative abundance of some beneficial microbial species, such as Arthrobacter and Gaiellales, in the cropping maize and continuous cropping of alfalfa were much higher than that in the meadow field. Moreover, the networks differ among different plant types, and also differ among different continuous cropping years of alfalfa, and topology of the networks suggested continuous planting of alfalfa promotes cooperation between bacteria, which facilitates the long growth of alfalfa and is beneficial to the soil.